629 CPVT and complete atrio-ventricular block: two faces of the same coin?. (8th December 2021) - Petrungaro, Mattia; Nesti, Martina; Cavaretta, Elena; Palamà, Zefferino; Scarà, Antonio; Martino, Annamaria; Robles, Antonio Gianluca; De Maio, Melissa; Romano, Silvio; Penco, Maria; Calò, Leonardo; Sciarra, Luigi
Abstract: Aims: Catecholaminergic polymorphic ventricular tachycardia (CPVT) is an electrical genetic disease characterized by induction of malignant ventricular arrhythmias during adrenergic stress in structurally normal hearts. CPVT is correlated to syncope or sudden cardiac death (SCD). Usually, it is caused by an autosomal dominant mutation in the cardiac ryanodine receptor (RyR2), an essential gene for Ca2+ homeostasis. Methods and results: Our case series refers to: a man (59 years) who came to our attention for a clinical check-up 4 years after implanting bicameral pacemaker at the age of 55 years for complete AV block; and his three sons (E. female 27 years; D. male 25 years; and B. female 17 years) who had evidence of polymorphic non-sustained ventricular tachycardia (NSVT) with increasing effort during stress test. The three sons performed cardiac MRI and underwent genetic test. All three were found to be carriers of the same microdeletion of the RYR 2 gene (1q43- extended for about 49 kb) at the genetic test. They also have non-compacted myocardium at cardiac MRI. The father was also found to be a carrier of the same genetic microdeletion, while the mother was negative to the genetic test. The man was diagnosed to be a carrier of the mutation 4 years after pacemaker implantation. Conclusions: Mutation of the RyR2 may have different phenotypic expressions and can be correlated to various clinical manifestations. CPVT is the most common one, and its prompt identification is crucial to prevent subjects from sport-related risks and to plan an efficient therapy. Our case series provides evidence for a careful consideration of such a genetic disorder even in presence of a major AV conduction disease in a relatively young subject. In the present case series, no major adverse events occurred. However, we can, in the aftermath, speculate that if a genetic disorder had been suspected when AV block occurred, a timely diagnosis could have been made earlier also for the sons.